2016
DOI: 10.1016/j.bbmt.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity of the Lee Chronic Graft-versus-Host Disease Symptom Scale as Assessed by Cognitive Interviews

Abstract: The Lee Chronic Graft-Versus-Host Disease (cGVHD) Symptom Scale has been recommended for use by the 2005 and 2014 NIH Consensus Conferences to capture chronic GVHD symptoms. Although the cGVHD Symptom Scale was previously validated, this study aims to re-examine the instrument’s content validity by exploring the clarity, comprehensibility, relevance and ease of use in a contemporary chronic GVHD sample, toward FDA qualification of this patient-reported outcomes (PRO) instrument as a drug development tool. Atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Recently, further work has been done to re-examine the validity of the LSS in a contemporary patient cohort, towards FDA qualification of this PRO measure as a drug development tool. The results show very positive responses from participants, who reported that the scale is clear and captures almost all of their symptoms (30). Although future studies may be needed to expand the populations studied, this study strongly supports the FDA qualification of this PRO measure.…”
Section: Pros In Chronic Gvhd: Progress Since 2010supporting
confidence: 60%
“…Recently, further work has been done to re-examine the validity of the LSS in a contemporary patient cohort, towards FDA qualification of this PRO measure as a drug development tool. The results show very positive responses from participants, who reported that the scale is clear and captures almost all of their symptoms (30). Although future studies may be needed to expand the populations studied, this study strongly supports the FDA qualification of this PRO measure.…”
Section: Pros In Chronic Gvhd: Progress Since 2010supporting
confidence: 60%
“…The LSS is a 30-item measure with one summary score and seven domains: skin, mouth, eye, lung, psycho-emotional, vitality and nutrition. 23 , 24 Higher scores indicate greater symptom burden. Half of the cases received the LSS with a 1-month recall period and half received a 1-week version; results were combined for analysis because there was no statistical difference between the aggregate scores for the two versions ( data not shown ).…”
Section: Methodsmentioning
confidence: 99%
“…This 30-item symptom assessment measures the negative effects of chronic GVHD on skin, vitality, lung, nutritional status, psychologic functioning, and eye and mouth symptoms, with higher scores indicating greater symptom burden. The Lee Symptom Assessment Scale is well validated [22] and frequently used in chronic GVHD research [23].…”
Section: Symptom Burdenmentioning
confidence: 99%